Study of the accelerated aging on aroma, color and physicochemical parameters of Tannat wines (INNOTEC, 2022)
In this work, different techniques were evaluated to achieve accelerated aging of the wine: ultrasound (US), gamma irradiation (RG) and high pressure (AP). The experimental conditions for each treatment were as follows: US, sequences of 30 and 60 minutes at 20 kHz; RG, three doses were analyzed (1, 3 and 6 kGy); for AP a constant pressure of 650 MPa was applied varying the application time (15, 30, 60 and 120 minutes). The wines were characterized by their basic physicochemical characteristics, their volatile profile (GC-MS) and color analysis (CIELAB). The same wine but without any treatment was used as a control. The results obtained showed that US treatment did not produce significant differences with respect to the control for all the conditions tested. For AP, significant differences were obtained with respect to the control in color (decrease in all the chromatic parameters) and content of volatile compounds (increase in the terpenes and esters contents). The GR treatment produced the greatest changes with respect to the control wine, with an increase in all the chromatic parameters with increasing radiation dose. The volatile profile showed an increase in 3-oxo-α-ionol, ho-diol and ethyl lactate content, all desirable changes during natural ageing.
Keywords: ultrasound; high pressure; gamma irradiation; Vitis vinifera; maturation